Role of NH4 ions in successive phase transitions of perovskite type (NH4)2ZnX4 (X = Cl, Br) by 1H MAS NMR and 14N NMR. Issue 21 (21st March 2018) - Lim, Ae Ran
Abstract : The 1 H chemical shifts and the spin-lattice relaxation time, T 1ρ, in the rotating frame of (NH4 )2 ZnX4 (X = Cl, Br) are observed in order to investigate local phenomena related to successive phase transitions. Abstract : The 1 H chemical shifts and the spin-lattice relaxation time, T 1ρ, in the rotating frame of (NH4 )2 ZnX4 (X = Cl, Br) are observed in order to investigate local phenomena related to successive phase transitions. The temperature dependence of T 1ρ values for 1 H showed a minimum, and the T 1ρ values for 1 H appeared to be governed by tumbling molecular motions at high temperatures. In addition, 14 N NMR spectra are studied in each phase of (NH4 )2 ZnX4 single crystals in the laboratory frame. The phase transition temperatures strongly affect the 14 N number of symmetry related nitrogen centers within the unit cell. The 1 H MAS NMR and 14 N NMR results are discussed to elucidate the roles of NH4 ions during the phase transitions of (NH4 )2 ZnX4 .